Antagonistic Potentiality of Some Soil Fungi Against Six Fungal Pathogens Isolated From Cotton (Gossypium Hirsutum L.) Seeds - Khatun, Amina; Shamsi, Shamim; Bashar, Abul (Journal of the Asiatic Society of Bangladesh, Science, 2020)
The antagonistic potentials of four soil filamentous fungi viz., Aspergillus flavus Link, A. fumigatus Fresenius, A. niger van Tieghem and Trichoderma viride Pers. against six pathogens isolated from 14 varieties of cotton (Gossypium hirsutum L.) were evaluated by "dual culture colony interaction”, volatile and non-volatile metabolites. In dual culture colony interaction, out of four soil fungi, T. viride was found be the most effective to control the growth of the cotton pathogens. T. viride showed the highest growth inhibition against Curvularia lunata, Fusarium moniliforme, Mucor sp. and Rhizoctonia solani. On the other hand A. niger showed the highest growth inhibition against Fusarium nivale and A. fumigatus showed the maximum growth inhibition against C. gloeosporioides. The highest inhibition of radial growth of C. lunata, F. nivale and F. moniliforme was observed might be due to the secretion of volatile metabolites of T. viride whereas, the maximum inhibition of radial growth of C. gloeosporioides was observed because of the volatile metabolites of A. flavus. Mucor sp. and R. solani were inhibited due to the volatile metabolites of A. fumigatus. The greatest radial growth inhibition of C. lunata and F. moniliforme were noticed in case of T. viride owing to the effect of non-volatile metabolites. On the other hand, the radial growth of C. gloeosporioides and F. nivale were inhibited highest amount for the effect of non-volatile metabolites of A. niger, whereas highest growth inhibition of Mucor sp. and R. solani was observed due to the non-volatile effect of A. fumigatus. The present investigation suggests that the isolates of Aspergillus and Trichoderma may be further exploited as potential biocontrol agents against the fungal pathogens of cotton in field trial. J. Asiat. Soc. Bangladesh, Sci. 46(2): 143-153, December 2020